South American giant short-faced bear (Arctotherium angustidens) diet: evidence from pathology, morphology, stable isotopes, and biomechanics - Soibelzon, Leopoldo Héctor (2014)
Arctotherium angustidens Gervais and Ameghino, 1880 (the South American giant short-faced bear) is known for being the earliest (Ensenadan Age, early to middle Pleistocene) and largest (body mass over 1 ton) of five described Arctotherium species endemic to South America. Here we assess the diet of this bear from multiple proxies: morphology, biomechanics, dental pathology, stable isotopes and a previous study using geometric morphometric methodology. Results favor the idea of animal matter consumption, probably from large vertebrates in addition to vegetable matter consumption. Most probably, active hunting was not the unique strategy of this bear for feeding, since its large size and great power may have allowed him to fight for the prey hunted by other Pleistocene carnivores. However, scavenging over mega mammal carcasses was probably another frequent way of feeding. South American short-faced bears adjusted their size and modified their diet through Pleistocene times, probably as a response to the diversification of the carnivore guild (from the few precursory taxa that crossed the Panamanian Isthmus during the Great American Biotic Interchange).